Analisis Perlakuan Disposal Aset Tetap Pada PT. X : Bayu Andita Kusuma1), Agus Susilo2) 1Program Studi Akuntansi, Politeknik Ubaya E-mail: bayuanditakusuma@gmail.com 2Program Studi Akuntansi Politeknik Ubaya E-mail: a_susilo@staff.ubaya.ac.id - Agus Susilo; Bayu Andita Kusuma (Jurnal Akuntansi dan Pajak, 2025)
This study aims to evaluate PT. X regarding the implementation of fixed asset disposal. Fixed asset disposal is an accounting process in which assets are derecognized or written off when they have reached the end of their useful life or no longer provide economic benefits to the company. This process is necessary to ensure that the financial statements remain fairly and accurately presented. The study employs a qualitative method by collecting data through financial report documentation and interviews with the company’s representative, namely a senior auditor from the Public Accounting Firm Heliantono and Partners, who is responsible for auditing PT. X. The findings reveal that the disposal of certain fixed assets at PT. X should have occurred between 2018 and 2021. However, the disposal was only carried out in 2023, involving a total derecognized asset value of IDR 809,972,979. The company determined that the useful lives and economic benefits of these assets had fully expired, and retaining them on the books would result in misrepresentation in the financial statements. This study also aligns with the latest Financial Accounting Standards, namely PSAK 16, which was updated and renumbered to PSAK 216, effective as of January 1, 2024. Based on the analysis, the disposal conducted by PT. X in 2023 was in accordance with applicable accounting principles. Nevertheless, it is recommended that the company consider revaluation of fixed assets to accurately assess their economic value. Through such revaluation, the company might have avoided premature disposal in prior years by identifying residual value or extended usability of assets.  Keywords : Fixed Asset Disposal, Financial Statements, PSAK 216, Fixed Assets, Asset Revaluation, PT. X, Accounting Principles.